Effect of extraction solvent and harvest time on recovery of bioactive compounds, antioxidant and cancer cell growth inhibition activities of Korean Camellia mistletoe : Antioxidant and anticancer activities of Camellia mistletoe - Min Young Kim (Journal of Tropical Life Science, 2023)
This study aimed to determine the phytochemical profiles, in vitro antioxidant and antiproliferative properties of Korean Camellia mistletoe (Korthalsella japonica (Thunb.) Engl.) depending on the harvest time (August and November) and solvent (100% methanol, 70% ethanol and hot water). The Camellia japonica L. mistletoe extracts were analyzed for contents of total phenol, flavonoid, total carotenoid and L-ascorbic acid, and antioxidant properties such as scavenging capacities (1,1-diphenyl-2-picrylhydrazyl (DPPH) and NO•), ferrous ion chelating and reducing power. Concurrently, the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used to assess the antiproliferative properties against human cancer cell lines; MCF (human breast cancer cells), Hela (human cervical cancer cells), A375 (human malignant melanoma cells), HCT116 (human colon cancer cells), HepG2 (human liver cancer cells) and A549 (human non-small cell lung adenocarcinoma cells). The results showed that extraction solvent and harvest time had significant impacts on antioxidant and anticancer activities, as well as selectivity for free phenolic compounds in Camellia japonica L. mistletoe. Among all the tested extracts the highest amounts of total phenolic and total flavonoids content were found in ethanol extracts of Camellia japonica L. mistletoe harvested in November, while the methanol extracts of Camellia japonica L. mistletoe collected in August showed the highest contents of total carotenoids and L-ascorbic acids compared to the other tested extracts. Additionally, the highest NO• radical scavenging activity was found in ethanol extracts, whereas the strongest DPPH radical scavenging activity was found in methanol extracts of Camellia japonica L. mistletoe harvested in November. Furthermore, methanol extracts showed much higher antiproliferative activity against all human cancer cells than ethanol extracts of Camellia japonica L. mistletoe harvested in November. In conclusion, the antioxidant and anticancer properties of Camellia japonica L. mistletoe showed significant dependence on the extraction solvent type and harvest time. With optimum harvest time and extraction solvent, they boast a wide range of promising applications in the medical, pharmaceutical, and food industries.